Vázlatpontok a magyar külpolitika három évtizedének oktatásához: BULLET POINTS FOR THE EDUCATION OF THREE DECADES OF HUNGARIAN FOREIGN POLICY - Gazdag, Ferenc (Közép-Európai Közlemények, 2020)
We are in 2020, but the conclusions of the Hungarian foreign policy’s three decades following the democratic transition has yet to be drawn. The tomes on the history and characteristics of the political system are jut being written in the workshops of political science (József Bayer, András Körösényi, János Simon). Some works have been published on certain policies, but an overview of the Hungarian foreign policy is still missing. The author of the present paper would like to contribute with some ideas to a future tome on the three decades of Hungarian foreign policy after the democratic transition.